1996
DOI: 10.1029/95tc02291
|View full text |Cite
|
Sign up to set email alerts
|

A flexural isostatic model of lithosphere shortening and foreland basin formation: Application to the Eastern Cordillera and Subandean belt of NW Argentina

Abstract: A numerical model of lithosphere shortening has been developed to combine flexural isostatic and structural balancing. This allows us to quantitatively reconcile lithosphere shortening, thrust sheet emplacement, and foreland basin formation. Lithosphere shortening is accommodated by thrusting in the upper crust and by distributed deformation in the lower crust and the lithospheric mantle. This leads to loading by thrust sheet emplacement, crustal thickening, and thermal perturbation. Additional loading and unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…This approach has the capability to integrate in an adequate way constraints provided by structural geology with basin modeling in compressional settings. Such constraints can result from analog modeling (see Brun and Nalpas 1996), computer modeling (see Sassi et al 1993;Zoetemeijer et al 1993;Roure and Sassi 1995;Toth et al 1996), seismic reflection data, and field studies in onshore and offshore basins (see Roure et al 1996b). These models can also be linked with the large-scale flexural models discussed above.…”
Section: Controls Of Thrusting On Foreland Basin Stratigraphymentioning
confidence: 98%
“…This approach has the capability to integrate in an adequate way constraints provided by structural geology with basin modeling in compressional settings. Such constraints can result from analog modeling (see Brun and Nalpas 1996), computer modeling (see Sassi et al 1993;Zoetemeijer et al 1993;Roure and Sassi 1995;Toth et al 1996), seismic reflection data, and field studies in onshore and offshore basins (see Roure et al 1996b). These models can also be linked with the large-scale flexural models discussed above.…”
Section: Controls Of Thrusting On Foreland Basin Stratigraphymentioning
confidence: 98%
“… Flemings and Jordan [1989] incorporated wedge‐progradation gradual loading and sedimentation. Later, Toth et al [1996] and Ford et al [1999] explicitly related loading with thrusting in the active margin of the sub‐Andean foreland and the western Alps, respectively. Many among these and other works found that the load derived from the present topography or the thrust kinematics cannot satisfactorily explain the basement deflection.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we propose a self‐consistent quantitative model for the evolution of the Guadalquivir Basin (southern Spain) linking the emplacement of the Betic Range, the subcrustal mass redistribution, and the rheology of the flexed lithosphere. For this purpose, we apply a numerical code based on Garcia‐Castellanos et al [1997] that allows the calculation of the flexural subsidence of a multilayered lithosphere (in a similar way to Waschbusch and Royden [1992] and Burov and Diament [1992, 1995]) when loaded by noninstantaneous thrusting and erosion/sedimentation processes (similar to Toth et al [1996]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early quantitative studies of foreland basin formation (Beaumont, 1981; Jordan, 1981), it is generally accepted that the sedimentary record of these basins is related to the flexural response of the continental lithosphere to orogen loading. Later numerical models incorporated non‐instantaneous wedge loading and sedimentation processes (Flemings & Jordan, 1989; Toth et al ., 1996; Ford et al ., 1999) finding that larger sedimentary basins are expected at higher transport rates and higher lithospheric rigidity (Flemings & Jordan, 1989). Other authors investigated the role of the lithospheric rheological stratification on the geometry of the sedimentary infill (Waschbusch & Royden, 1992; Garcia‐Castellanos et al ., 1997, 2002).…”
Section: Introductionmentioning
confidence: 99%